Critically investigate the effect of Institutional Quality, Economic Growth and Carbon Dioxide Emission in Pakistan - Allahrakha, Rubina; Sheikh, Salman Masood; Rahman, Saif ur (Pakistan Journal of Humanities and Social Sciences, 2023)
This study was designed to have an insight into the literature, both theoretical and empirical, on the relationship of dependent variable Carbon dioxide (CO2) and independent variables institutional quality (IQ), gross domestic product (GDP), and foreign direct investment (FDI) in the context of developing economies growth from 2000 to 2023. It is an overview of the related published literature about Pakistan. This article is focused using theoretical techniques that explain how and why certain techniques operate and identifies three further dimensions for further research. It’s a huge policy challenge to manage CO2 emissions with advanced technology alone. As per report of (IEA) international energy agency 2020, Pakistan has reallocated the National Clean Fund to compensate for the reforms. The FDI inflows & IQ are pivitol in attaining the sustainable environment. Higher FDI invariably leads to higher emissions, ensuring IQ initiatives both in public and private sector will mitigate this negative impact. Tagging incentive to eco-friendly ambitious technology initiative help environmental sustainability. Variables like degree of industrial development, quality of trained labor force, and overall rate of literacy as factor additional variable that determines the degree/ amount CO2 production, these are beyond the scope of this study as data is not available, and it shall be the focus of further exploration.